Near infrared hyperspectral imaging as detection method for pre-germination in whole wheat, barley and sorghum grains - Engelbrecht, Paulina (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc Food Sc)--University of Stellenbosch, 2011.